2017
DOI: 10.3233/isu-170828
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of health literacy to mHealth

Abstract: Abstract. This paper examines the importance of health literacy to the design and use of mobile digital health information technology (mHealth) applications. Over the past two decades mHealth has evolved to become a major health communication channel for delivering health care, promoting health, and tracking health behaviors. Yet, there are serious communication challenges that must be addressed concerning the best way to design and utilize mHealth application to achieve key health promotion goals, including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 50 publications
(86 reference statements)
0
36
0
1
Order By: Relevance
“…In turn, this may increase the proportion of the population that trusts collecting personal health information on digital devices [ 26 ]. Perceived utility of mHealth technologies for health or behavioral tracking may also increase among nonowners and nonusers and former owners and users as mHealth technologies advance in their functionality, especially if approaches such as ensuring sociocultural relevancy [ 27 ] and person-centered design [ 28 , 29 ] are considered throughout mHealth technology development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, this may increase the proportion of the population that trusts collecting personal health information on digital devices [ 26 ]. Perceived utility of mHealth technologies for health or behavioral tracking may also increase among nonowners and nonusers and former owners and users as mHealth technologies advance in their functionality, especially if approaches such as ensuring sociocultural relevancy [ 27 ] and person-centered design [ 28 , 29 ] are considered throughout mHealth technology development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our findings related to mHealth nonowners and nonusers suggest that clinical and public health practitioners could consider alternatives to mHealth interventions to track and promote health behavior change, especially among less educated older men. However, they also call to mind the importance of ensuring that not owning or using mHealth technologies for health or behavioral tracking is not due to barriers that can be addressed, such as digital health literacy [ 28 , 30 - 32 ]. Researchers and organizations are addressing some of these issues through programs such as RecycleHealth [ 31 , 33 ], American Association of Retired Persons Tek workshops [ 34 , 35 ], and The Wellness Group [ 36 ], with measurable beneficial effects on health and behavioral outcomes [ 31 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although language options (ie, Catalan and Spanish) were found in the app Pukono , these languages are not relevant to the Asian marketplace. The implications of the possible language barrier in mHealth apps have been discussed in a previous study [ 43 ]. The study showed that most mobile phone users prefer to use apps in their primary language [ 44 ], which can lead to greater user engagement and prevent the misinterpretation of health information.…”
Section: Discussionmentioning
confidence: 99%
“…eHealth literacy is defined as the ability to search, find, understand, evaluate, and use health information available via electronic resources [53]. As eHealth and mHealth tools for MS can improve self-management skills [10], it can be assumed that higher eHealth literacy may increase the likelihood of effectively using electronic resources such as MS apps [54].…”
Section: Methodsmentioning
confidence: 99%